2021
DOI: 10.1111/1365-2664.13889
|View full text |Cite
|
Sign up to set email alerts
|

Blue consequences of the green bioeconomy: Clear‐cutting intensifies the harmful impacts of land drainage on stream invertebrate biodiversity

Abstract: 1. Growing bioeconomy is increasing the pressure to clear-cut drained peatland forests. Yet, the cumulative effects of peatland drainage and clear-cutting on the biodiversity of recipient freshwater ecosystems are largely unknown.2. We studied the isolated and combined effects of peatland drainage and clearcutting on stream macroinvertebrate communities. We further explored whether the impact of these forestry-driven catchment alterations to benthic invertebrates is related to stream size. We quantified the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The few previous studies that have addressed the impacts of peatland management on benthic biodiversity have generally shown that drainage-induced changes to stream habitat and/or water quality reduce invertebrate diversity in recipient streams (Ramchunder et al 2012;Brown et al 2019;Rajakallio et al 2021). Similarly, in a study of 18 streams in northern Sweden, Jonsson et al (2017) concluded that DOC and pH were the main drivers of benthic invertebrate richness and community composition.…”
Section: Discussionmentioning
confidence: 98%
“…The few previous studies that have addressed the impacts of peatland management on benthic biodiversity have generally shown that drainage-induced changes to stream habitat and/or water quality reduce invertebrate diversity in recipient streams (Ramchunder et al 2012;Brown et al 2019;Rajakallio et al 2021). Similarly, in a study of 18 streams in northern Sweden, Jonsson et al (2017) concluded that DOC and pH were the main drivers of benthic invertebrate richness and community composition.…”
Section: Discussionmentioning
confidence: 98%
“…We draw on our experience working on riparian buffers with other researchers, managers, practitioners and policymakers in Canada (the province of British Columbia—BC), Finland and Sweden (e.g. Hasselquist et al., 2021; Jyväsjärvi et al., 2020; Kuglerová et al., 2020; Rajakallio et al., 2021; Richardson et al., 2012; Richardson & Béraud, 2014), but our conclusions are likely applicable to other forestry jurisdictions. We write this perspective to highlight that a dialogue among policymakers, managers and scientists is urgent to identify key priorities and actions aimed at improving local best‐management‐practices for freshwater and riparian protection.…”
Section: Introductionmentioning
confidence: 99%